“I want my eyes…” : Blindness and Perception of the World in Polish Translations of Charles Dickens’s The Cricket on the Hearth - Budrewicz, Aleksandra (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2018)
The article discusses Polish translations of Charles Dickens’s The Cricket on the Hearth in terms of the vocabulary related to the blind girl Bertha, one of The Cricket’s characters. The translations are compared and juxtaposed; the way their authors managed to talk about Bertha’s disability is presented within the context of both political correctness and the practices of the Polish publishing houses in the twentieth century.